Synthesis of polyaniline-based inks for inkjet printed devices: electrical characterization highlighting the effect of primary and secondary doping. (18th August 2015) - Chiolerio, Alessandro; Bocchini, Sergio; Scaravaggi, Francesco; Porro, Samuele; Perrone, Denis; Beretta, Davide; Caironi, Mario; Fabrizio Pirri, Candido
Abstract: Engineering applications for printed electronics demand solution processable electrically conductive materials, in the form of inks, to realize interconnections, piezoresistive pressure sensors, thermoresistive temperature sensors, and many other devices. Polyaniline is an intrinsically conductive polymer with modest electrical properties but clear advantages in terms of solubility and stability with temperature and in time. A comprehensive study, starting from its synthesis, primary doping, inkjet printing and secondary doping is presented, with the aim of elucidating the doping agent effects on its morphology, printability and electronic performance.